CO2 Utilization for the dyeing of yak hair: Fracture behaviour in supercritical state. (March 2017) - Zheng, Huanda; Zhang, Juan; Liu, Miao; Yan, Jun; Zhao, Hongjuan; Zheng, Laijiu
Graphical abstract: Highlights: Ecofriendly dyeing of yak hairs was conducted in supercritical carbon dioxide. Effects of different system parameters on the fracture behaviour of yak hairs were investigated. Fracture behaviour of yak hairs in supercritical carbon dioxide was proposed. Abstract: In this paper, using carbon dioxide as a dyeing medium, some basic color and mechanical behaviour data for yak hairs were firstly obtained with different parameters. The effects of system temperature, pressure, time and depressurization rate on yak hairs were investigated in terms of the color strength, the short fiber content, the breaking strength and the elongation at break. The results indicated that the short fiber content of yak hairs was increased with the raising of system temperature, pressure, time as well as depressurization rate, while the breaking strength and the elongation at break of yak hairs were decreased with the increase of system temperature, time as well as depressurization rate. Moreover, supercritical carbon dioxide for the fracture mechanism of yak hairs was proposed based on the Bernoulli's principle and Boyle's Law.